Synonymy and misidentification of three Hahnia species (Araneae: Hahniidae) from China - Zhang, Zhi-Sheng; Zhang, Yao-Guang (Zootaxa, 2013)
The type specimens of two Hahnia species, H. maginii Brignoli, 1977 and H. thorntoni Brignoli, 1982 were examined to determine the identification of Hahniidae from South China. Hahnia thorntoni is found to be a senior synonym of H. flagellifera Zhu, Chen & Sha, 1989, while the paratype male of H. thorntoni belongs to another species, H. zhejiangensis Song & Zheng, 1982. Chinese specimens previously identified as H. maginii probably belong to H. thorntoni. The female and male specimens of H. yueluensis Yin & Wang, 1983 were mismatched and misidentified; the female holotype and paratype belong to H. thorntoni and male allotype to H. zhejiangensis.